Biology - Mason, Kenneth A.; Losos, Jonathan B.; Duncan, Tod (New York, NY : McGraw Hill LLC, 2023)
"With the new 13th edition, Raven and Johnson's Biology continues the momentum built over the last four editions. We continue to provide an unmatched comprehensive text fully integrated with a continually evolving, state-of-the-art digital environment. We have used this revision to recommit ourselves to our roots as the majors biology text that best integrates evolution throughout. We have added material emphasizing the relevance of evolution throughout the ecology section, not only in all four ecology chapters, but also in the chapters on behavior and conservation biology. In the animal form and function section we have done extensive revision to modernize, and to emphasize evolution in the context of physiology. Important contributions to this effort came from Dr. Charles Welsh (Duquesne University), who provided his knowledge and experience to this important section. We have also moved the examples and insights from the chapter devoted to the evolution of development to place them into the appropriate context throughout the book. This emphasizes the importance of evolution and development by continually providing examples rather than gathering them together in a single chapter"--
Includes bibliographical references and index.
Keywords: Biology -- Textbooks; Zoology